Analysis of Influence of Characteristics of Islamic Supervisory Board toward Islamic Financial Performance - Rifai, Achmad; Asrori, Asrori (Universitas Negeri Semarang, 2017)
Tujuan dari penelitian ini adalah untuk untuk menguji dan menganalisis karakteristik Dewan Pengawas Syariah yang direpresentasikan dengan DPS Scientific Backgrounds, Attendance of DPS Meeting, dan DPS Multi-positions terhadap Islamic Financial Performance melalui kesesuaian pelaporan syariah sebagai mediasi. Populasi penelitian adalah seluruh bank umum syariah yang ada Indonesia periode tahun 2011- 2015. Jumlah sampel yang diuji sebanyak 8 bank umum syariah yang dipilih dengan metode purposive sampling. Penelitian ini menganalisis laporan tahunan bank umum syariah dengan metode content analysis. Metode analisis yang digunakan adalah Structural Equation Modelling (SEM) dengan Partial Least Square (PLS) Path Modelling dengan alat analisis SmartPLS 3.0. Hasil penelitian menunjukkan bahwa Attendance of DPS Meeting dan kesesuaian pelaporan syariah berpengaruh secara langsung terhadap Islamic Financial Performance. Variabel DPS Scientific Backgrounds dan rangkap jabatan tidak berpengaruh secara signifikan terhadap Islamic Financial Performance. Sedangkan variabel kesesuaian pelaporan syariah berpengaruh positif dan signifikan memediasi hubungan DPS Scientific Backgrounds terhadap Islamic Financial Performance, namun tidak mampu memediasi hubungan Attendance of DPS Meeting dan DPS Multi-positions terhadap Islamic Financial Performance. The purpose of this is study to examine and analyze the characteristics of the Sharia Supervisory Board (SSB) is represented by the SSB scientific background, SSB meeting attendance, and SSB dual position on Islamic financial performance through sharia conformance reporting as mediation. The population is all existing Islamic banks Indonesia period 2011-2015. The number of samples tested by 8 Islamic commercial bank selected by purposive sampling method. This study analyzed the annual reports of Islamic banks with content analysis. The analytical method used is Structural Equation Modelling (SEM) with Partial Least Square (PLS) path modeling analysis tool SmartPLS 3.0. The results showed that the presence of SSB meeting attendance and sharia conformance reporting have a direct impact on the Islamic financial performance. SSB scientific background variables and SSB dual position do not significantly affect the Islamic financial performance. While variable sharia conformance reporting positive and significant effect mediates the relationship DPS scientific background to the Islamic financial performance, but is not able to mediate the association SSB meeting attendance and SSB dual position on the Islamic financial performance. Based on the result, it can be conclude that SSB meeting attendance and sharia conformance reporting have effect on Islamic financial performance.